The biocrystalloid structure of man: an extracellular theory - Ermolenko,, Alexander E.; Perepada, Elena A. (Acta Biomedica Atenei Parmensis, 2007)
Medical science based solely on the postulates of the cellular theory does not describe the structure and functions of biological organisms in full or meet the needs of modern medicine. Biological organisms, man included, can be regarded as biocrystalloids that are composites of crystals and paracrystalline media at the level of the whole organism and individual cells alike. The core component of biocrystalloids is represented by extracellular components of the connective tissue. The paper describes major features of biocrystalloids and highlights their similarity to mineral organisms in which a growing or weathering crystal also regulates the flows of the paracrystalline medium. The paper concludes that further research into the force fields of a biocrystalloid will allow developing new diagnostic and treatment modalities.